1994
DOI: 10.1007/bf02426696
|View full text |Cite
|
Sign up to set email alerts
|

Indium-111 pentetreotide in the diagnostic work-up of patients with bronchogenic carcinoma

Abstract: In a prospective study we examined 38 patients with primary bronchogenic carcinoma to validate the use of indium-111 pentetreotide (IPT) as a diagnostic tool. Of these 38 patients, 25 had small cell lung cancer (SCLC) and 13, non-small cell lung cancer (NSCLC). The aim of the study was to investigate whether (a) the disease can be reliably detected, (b) IPT allows differentiation between SCLC and NSCLC and (c) IPT provides further information on metastatic disease. After giving their informed consent the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Two further studies have confirmed that [ 111 In]pentetreotide scintigraphy is effective in the localization of NSCLC tumors, detecting the primary tumor in 40 of 40 [86] and 10 of 13 patients, respectively [87]. However, metastatic sites of disease were not as frequently detected, thereby demonstrating the limitations of the technique.…”
Section: Nsclc [ 111 In]pentetreotide Imagingmentioning
confidence: 91%
“…Two further studies have confirmed that [ 111 In]pentetreotide scintigraphy is effective in the localization of NSCLC tumors, detecting the primary tumor in 40 of 40 [86] and 10 of 13 patients, respectively [87]. However, metastatic sites of disease were not as frequently detected, thereby demonstrating the limitations of the technique.…”
Section: Nsclc [ 111 In]pentetreotide Imagingmentioning
confidence: 91%
“…Pituitary tumors (Kwekkeboom et al 1999) GEPNETs Gastrinomas (De Kerviler et al 1994, Gibril et al 1996 Nonfunctioning endocrine pancreatic tumors (Krenning et al 1993, Lebtahi et al 1997 Functioning endocrine pancreatic tumors except insulinomas (Krenning et al 1993, Lebtahi et al 1997 Carcinoids (Kwekkeboom et al 1993a, Westlin et al 1993, Ahlman et al 1994, Kalkner et al 1995 Paragangliomas (Kwekkeboom et al 1993b, Telischi et al 2000, Duet et al 2003) Small cell lung cancer (Kirsch et al 1994, Kwekkeboom et al 1994, Bombardieri et al 1995, Reisinger et al 1998 Meningiomas (Haldemann et al 1995) Sarcoidosis and other granulomatous diseases (Vanhagen et al 1994, Kwekkeboom et al 1998) Graves' disease and Graves' ophthalmopathy (Postema et al 1994, Krassas et al 1995 Intermediate sensitivity Insulinoma (Krenning et al 1993, Zimmer et al 1996 Medullary thyroid carcinoma (Kwekkeboom et al 1993c, Tisell et al 1997, Adams et al 1998 PET with these ligands was reported to be more sensitive than SRI with [ 111 In-DTPA 0 ]octreotide. These PET ligands, however, have to be synthesized in the close vicinity of or in the hospital where the administration to the patient is to take place.…”
Section: High Sensitivitymentioning
confidence: 99%
“…Therefore we postulated the use of radiolabelled OCT to localize the site of the tumour and to discriminate between ASPA and ectopically secreting ACTH tumour. The premise for our attempt was based on recent reports showing in vivo uptake of radiolabelled OCT in a large percentage of bronchial and abdominal carcinoids as well as in SCLC and other neuroendocrine tumours (10,11).…”
Section: European Journal Of Endocrinology (1997) 137mentioning
confidence: 99%